Synthesis and characterization of alumina fibers using solution blow spinning - Mota,M. F. (2019)
Abstract This work shows the successful production of alumina nanofibers after thermal treatment of solution blow spun hybrid fibers. These nanofibers were converted into γ-Al2O3 and α-Al2O3 after the thermal treatment in air between 500 to 1200 °C. The X-ray diffraction patterns presented all the characteristics of the γ and α phases of alumina. In addition, the scanning electron micrographs showed alumina nanofiber diameters varying between 200 and 270 nm for different temperatures. The results demonstrated that the solution blowing spinning method is efficient to produce alumina nanofibers.